Identification of early onset pre-eclampsia related key genes via bioinformatic analysis. (2022) - Huang, Zhengrui; Chen, Ruiping; Zhou, Yixuan; Wei, Yiling; Liu, Haixia; Zhang, Ping; Wang, Jingyun; Ding, Yuzhen; Yang, Xiaofeng; Sun, Lu; Shi, Meiting; Gao, Yudie; et al.
Abstract: Background: Pre-eclampsia is a common pregnancy-specific disease. In this study, we used comprehensive bioinformatics to screen key genes related to the development of pre-eclampsia and explore their potential connections. Methods: Two data sets GSE44711 and GSE30186 from the GEO database were used. The experimental group data set GSE44711 includes 16 samples (8 normal group samples and 8 early-onset PE group samples); the validation group data set GSE30186 includes 12 samples (6 Samples from the normal group and 6 samples from the PE group). Use the limma R package to analyze the difference between the two data sets, perform enrichment analysis, GO and KEGG analysis on the experimental group data set GSE44711, then obtain the hub gene by cytoscape, and verify the Hub gene in the validation data set GES30186. Results: 826 DEGs were identified from GSE44711, including 458 up-regulated genes and 368 down-regulated genes; The 6 Hub genes (CXCR6, CD3D, CD8A, CD69, and IL5) identified are considered to have high credibility. Conclusion: Through our analysis, the functional difference between early onset preeclampsia and normal pregnancy patients was explained, and the Hub genes CXCR6, CD3D, CD8A, CD69 and IL5 were determined. Highlights: Significant hub genes and hub modules were identified in PE. Five less researched Hub genes (CXCR6, CD3D, CD8A, CD69, IL5) are predicted to be potential crucial genes which may play vital roles in EOPE.